Enhancing English Proficiency Through the 'One Day in English' Program: A Case Study at SMAN 1 Sidrap - Sitti Aisa; Sam Hermansyah; Syeh Junaidi Usman; Citra Karisma; Kartini; Muhammad Anugrah Nasruddin (Edumaspul: Jurnal Pendidikan, 2025)
English proficiency is a crucial skill in the era of globalization, yet high school students often face challenges in actively practicing the language. This study examines the implementation and effectiveness of the "One Day in English" program at SMAN 1 Sidrap. The program adopts an immersive learning approach where students are required to use English throughout the day in various interactive activities. These activities include group discussions, presentations, daily conversations, and games aimed at enhancing both oral and written communication skills.Using observational methods and pre-and post-program assessments, the study evaluates improvements in students' English language abilities. The findings reveal significant progress in speaking fluency, vocabulary comprehension, and overall confidence in using English. Moreover, the interactive nature of the program fostered active student participation and created a supportive learning environment.This research highlights the potential of immersive learning strategies in addressing barriers to effective English learning. It offers a practical framework for schools to adopt similar programs to enrich language learning experiences and build students’ confidence in real-world communication.